Osteoking Decelerates Cartilage Degeneration in DMM-Induced Osteoarthritic Mice Model Through TGF-β/smad-dependent Manner - Houfu Ling; Houfu Ling; Qinghe Zeng; Qinghe Zeng; Qinwen Ge; Qinwen Ge; Jiali Chen; Wenhua Yuan; Rui Xu; Rui Xu; Zhenyu Shi; Zhenyu Shi; et al. (Frontiers Media S.A., 2021)
Osteoarthritis (OA) is a common disease characterized by cartilage degeneration. In recent years much attention has been paid to Traditional Chinese Medicine (TCM) since its treatments have shown efficacy for ameliorating cartilage degradation with mild side effects. Osteoking is a TCM prescription that has long been used in OA treatment. However, the exact mechanism of Osteoking are not fully elucidated. In the current study, destabilization of the medial meniscus (DMM)-induced OA mice was introduced as a wild type animal model. After 8 weeks of administration of Osteoking, histomorphometry, OARSI scoring, gait analysis, micro-CT, and immunohistochemical staining for Col2, MMP-13, TGFβRII and pSmad-2 were conducted to evaluate the chondroprotective effects of Osteoking in vivo. Further in vitro experiments were then performed to detect the effect of Osteoking on chondrocytes. TGFβRIICol2ER transgenic mice were constructed and introduced in the current study to validate whether Osteoking exerts its anti-OA effects via the TGF-β signaling pathway. Results demonstrated that in wild type DMM mice, Osteoking ameliorated OA-phenotype including cartilage degradation, subchondral bone sclerosis, and gait abnormality. Col2, TGFβRII, and pSmad-2 expressions were also found to be up-regulated after Osteoking treatment, while MMP-13 was down-regulated. In vitro, the mRNA expression of MMP-13 and ADAMTS5 decreased and the mRNA expression of Aggrecan, COL2, and TGFβRII were up-regulated after the treatment of Osteoking in IL-1β treated chondrocytes. The additional treatment of SB505124 counteracted the positive impact of Osteoking on primary chondrocytes. In TGFβRIICol2ER mice, spontaneous OA-liked phenotype was observed and treatment of Osteoking failed to reverse the OA spontaneous progression. In conclusion, Osteoking ameliorates OA progression by decelerating cartilage degradation and alleviating subchondral bone sclerosis partly via the TGF-β signaling pathway.